Penyesuaian Diri Menjelang Pensiun Pada Guru PNS Golongan IV/A di Kabupaten Grobogan - Wanodya, Husnun Nadidah; , Dr. Wiwien Dinar Pratisti, M.Si, Psi (2016)
This study discusses the adjustment to retirement on civil servant teachers level IV/a in Grobogan, aims to find and describe the adjustment to retirement on civil servant teachers level IV/a in Grobogan. The approach in this study used qualitative methods with six respondents. Selection of the informants by purposive sampling. Measurements were made by using interviews with teachers of less than one year to five years of pension and leveled IV/a in Grobogan. Methods of data analysis used in this study is the organization of data, coding, determine the theme, do the categories, and describe the categories. The results showed: 1) civil servant teachers level IV/a in Grobogan have positive adjustment to face and resolve wisely, able to appreciate and be grateful for life given by God, sure can be existence in society, useful for families and others, and more religious 2) decrease of income did not make the candidates of retired civil servant discouraged because at the age about fifty five to sixty years had no much dependents living even their children already earn their own money 3) family support help adjustment the candidates of retired to be more ready, like discussions pension plans.